Recurrent ear discharge in primary care: exploring the possibility of cholesteatoma - a case report - Abdul Rashid, Aneesa; Mohd Nor, Khadijah; Liang, Loh Tze; Hashim, Muhammad Farid; Hassan, Faezah (International Journal of Human and Health Sciences, 2024)
Cholesteatoma is a benign lesion of the keratin-producing squamous epithelium, most commonly arising in the middle ear and mastoid. It is rarely found within the external auditory canal. It presents mainly as unilateral lesions and is often destructive and locally invasive. Hence, early detection and referral to an otorhinolaryngology specialist are warranted due to its grave sequelae. This report is about a rare and atypical case of an external ear canal cholesteatoma (EECC) in a young patient. The diagnosis and referral were delayed due to the nature of the disease that resembles an infection, the rarity and atypical presentation of the case, and a low index of suspicion. Therefore, a high index of suspicion based may lead to a timely diagnosis, management, prevention of serious complications, and optimal preservation of ear function